2017
DOI: 10.11604/pamj.2017.27.38.11873
|View full text |Cite
|
Sign up to set email alerts
|

L’utilisation de l’approche CTC: quel impact sur la couverture vaccinale lors de la campagne préventive de vaccination contre la méningite A avec le MenAfriVac au Togo en 2014 ?

Abstract: IntroductionUne campagne de vaccination contre la méningite A avec le vaccin MenAfriVac a été organisée dans les quatre régions septentrionales du Togo du 28 novembre au 07 décembre 2014. L'approche CTC a été utilisée pour la première fois à une grande échelle pour la campagne de vaccination dans dix districts sanitaires du Togo. L'objectif de cette étude était d'estimer la couverture vaccinale et, de déterminer l'effet de l'utilisation de la Chaîne à Température Contrôlée (CTC) sur ces couvertures vaccinales.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The CTC approach was first used on a large scale in 2014 in a vaccination campaign in 10 health districts in Togo. A survey carried out in Togo showed that the use of this approach did not have a negative impact on the vaccination coverage, and there were no significant differences in coverage in districts with CTC or in districts without CTC [8]. The CTC approach was also used in selected districts in Benin, Democratic Republic of the Congo, Côte d’Ivoire, Mauritania, and South Sudan.…”
Section: Methodsmentioning
confidence: 99%
“…The CTC approach was first used on a large scale in 2014 in a vaccination campaign in 10 health districts in Togo. A survey carried out in Togo showed that the use of this approach did not have a negative impact on the vaccination coverage, and there were no significant differences in coverage in districts with CTC or in districts without CTC [8]. The CTC approach was also used in selected districts in Benin, Democratic Republic of the Congo, Côte d’Ivoire, Mauritania, and South Sudan.…”
Section: Methodsmentioning
confidence: 99%
“…Two studies looked at the increased immunization coverage and other benefits of ‘off-label’ use of vaccines (Hepatitis B) outside the cold chain [ 22 , 23 ]. So far MenAfriVac vaccine, the first to be licensed by the WHO for use in ambient temperatures subject to meeting certain conditions – controlled temperature chain; has been extensively studied [ 19 , 20 , 24 ]. The study characteristics are summarized in Table 1 , and the key findings and limitations are summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Six of the articles in this review studied and reported on the (potential) benefits or otherwise of keeping vaccines under CTC conditions [ 18 - 21 , 24 , 26 ]. Two of the studies were non-randomized trials with one that explored the economic evaluation of the controlled temperature chain approach for vaccine logistics during the meningitis A vaccine campaign in Togo using CTC vaccines, while the other was a field-based evaluation of adverse events following immunization (AEFI) from the same MenAfriVac (CTC) mass campaign conducted in Benin republic [ 20 , 26 ]; two articles were cross-sectional studies with one being an immunization coverage survey that assessed the impact of the vaccine administered CTC in Togo in 2014, and the second study examined the benefits of delivering Meningitis A (MenAfriVac) vaccines in a controlled temperature chain in the Benin Republic following a mass immunization campaign [ 21 , 24 ]; and one study used cross-sectional study data to model the economic benefits of MenAfriVac vaccine stored CTC in three regions of Chad republic where over 1.8 million eligible were vaccinated in December 2011 [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations